Carex parva and Carex scabrirostris adopt diverse response strategies to adapt to low-light conditions - Liu, Wanting; Fan, Rong; Yang, Siyu; Chen, Sibo; Huang, Yulin; Ji, Wenli (Frontiers in Plant Science, 2024)
In recent years, the visible light intensity of lawns has significantly decreased due to obstructions caused by urban shading objects, such as architectural facilities and dense vegetation. Carex has a competitive advantage over other turfgrass in low light conditions and extensive management. Therefore, exploring their survival strategy in low light environments is of great significance. This study focuses on two species of Carex, Carex parva and Carex scabrirostris, investigates their response to low light conditions by simulating urban lawn conditions and examines the varying strategies of these two Carex species. Additionally, evaluation indicators closely correlating with the photosynthetic capacity of Carex were screened. The results showed that: (a) Peroxidase activity, specific leaf area, and relative water content are key factors influencing the photosynthetic capacity of the two Carex species. (b) Under low light conditions, photosynthetic parameters, leaf physiological indicators, and biomass allocation of the two Carex species were significantly affected. Both Carex species increased their investment in leaf biomass, maintained lateral root growth, and cleared reactive oxygen species to maintain their physiological balance. (c) In terms of response strategies, C. scabrirostris is a high-photosynthesis investing species with high productivity under low light conditions, whereas C. parva exhibits minimal response, indicating a slow investment. C. scabrirostris has greater potential for application in low-light environments compared to C. parva.These results provide a theoretical basis for the cultivation and application of these two Carex species, as well as the expansion of turfgrass germplasm resources.In recent years, lawns have played an increasingly significant role in landscape greening (Thompson and Kao-Kniffin, 2019), providing not only social benefits and ecosystem services to the urban environment but also substantial economic and ecological benefits (Trammell et al., 2019). Currently, urban buildings, artificial structures, and dense tree canopies have created numerous shaded areas, resulting in a significant reduction in visible light intensity within cities (Francini et al., 2023).However, most types of turfgrass do not adapt well to excessively shaded environments (Zhang et al., 2016). Given that light conditions are an important factor restricting turfgrass growth in urban environments, selecting a shade-tolerant turfgrass species is imperative (Fu et al., 2020).